The teaching practices of novice teachers at the secondary level (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2019)
The results of a research oriented towards the analysis of professional practice are synthesized, in terms of the knowledge of the discipline and the ways of selecting the contents and strategies for teaching, which are handled by beginning teachers. From the observations and the teaching narratives it was detected that the first problematic that worries the beginners (in a 100% of the surveys) consisted in the relations with the students. In a second moment issues related to teaching arose. The specific focus of the analysis on ‘the relation between the knowledge of the subject and the ways of selecting the contents to teach’ was observed the coherence between both. In addition, in the interviews they highlighted (100%) the excellent academic training received, which facilitates the formulation of objectives. A recurrent problem that was detected and manifested as a difficult obstacle to solve is the preparation of didactic plans and sequences, because each educational institution establishes precise provisions that differ from one establishment to another, despite the directives of the provincial public prosecutor. Regarding didactic strategies, it was observed the concern of the novices to implement innovations in the classes with the use of ICT, although with limitations.
Keywords: initial professional practice; professional teaching knowledge; professional identity; implicit theories